Правила тлумачення Галахи (Єврейського релігійного права). - Цвігун, Л.А.; Цвигун, Л.А.; Cvigun, L (My University, 2011)
In the article the basic rules of interpretation of Halakha – traditional ju- daic law, which consists of rules and establishments of judaism, that regulates religious, domestic and public life of jews, are analyzed and examined. Not only description of rules but also practical example of their application is given. The rules of interpretation of Halakha do possible applications of religious norms in modern society, as adjust them to the changing social conditions.
Цвігун, Л.А. Правила тлумачення Галахи (Єврейського релігійного права). / Л.А.Цвігун // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2011. - Вип. 43. - С. 257 - 267.
Keywords: Іудейське право; Тлумачення Галахи; Єврейське релігійне право; Эврейское религиозное право; Толкование Галахи; Иудейское право; Judaic law; The interpretation of Halacha; Evreyskoe religious right